Heat export from the tropics drives mid to late Holocene palaeoceanographic changes offshore southern Australia. (15th January 2018) - Perner, Kerstin; Moros, Matthias; De Deckker, Patrick; Blanz, Thomas; Wacker, Lukas; Telford, Richard; Siegel, Herbert; Schneider, Ralph; Jansen, Eystein
Abstract: The Leeuwin Current (LC), an eastern boundary current, transports tropical waters from the Indo-Pacific Warm Pool (IPWP) towards southern latitudes and modulates oceanic conditions offshore southern Australia. New, high-resolution planktic foraminifer assemblage data and alkenone-derived sea surface temperatures (SST) provide an in-depth view on LC variability and mechanisms driving the current's properties during the mid to late Holocene (last c. 7.4 ka BP). Our marine reconstructions highlight a longer-term mid to late Holocene reduction of tropical heat export from the IPWP area into the LC. Mid Holocene ( c. 7.4 to 3.5 ka BP) occurrence of high SSTs (>19.5 °C), tropical planktic foraminifera and a well-stratified water column document an enhanced heat export from the tropics. From c. 3.5 ka BP onwards, a weaker LC and a notably reduced tropical heat export cause oceanic cooling offshore southern Australia. The observed mid to late Holocene trends likely result from large-scale changes in the IPWP's heat storage linked to the El Niño-Southern Oscillation (ENSO) phenomenon. We propose that a strong and warm LC occurs in response to a La Niña-like state of ENSO during the mid Holocene. The late Holocene LC cooling, however, results from a shift towards an El Niño-like state and a more variable ENSO system that causes cooling of the IPWP. Superimposed on these longer-term trends we find evidence of distinct late Holocene millennial-scale phases of enhanced El Niño/La Niña development, which appear synchronous with northern hemispheric climatic variability. Phases of dominant El Niño-like states occur parallel to North Atlantic cold phases: the '2800 years BP cooling event', the 'Dark Ages' and the 'Little Ice Age', whereas the 'Roman Warm Period' and the 'Medieval Climate Anomaly' parallel periods of a predominant La Niña-like state. Our findings provide further evidence of coherent interhemispheric climatic and oceanic conditions during the mid to late Holocene, suggesting ENSO as a potential mediator. Highlights: New proxy records from offshore southern Australia cover the last 7.4 ka BP. SST and stratification changes link to Leeuwin Current (LC) properties. LC variability is driven by changes in tropical heat export from IPWP. Variations in tropical heat export links to millennial-scale ENSO state changes. Late Holocene IPWP heat export is coherent with changes in the northern hemisphere.